Elemental profiling of the root samples of six species of the genus Sida L - G Ashwathy; Krishnakumar K (Journal of Trace Elements and Minerals)
Introduction: Sida L. is a medicinally important genus comprising many species used in the traditional systems of medicine in different parts of the world. The present study deals with the elemental analysis of the root samples of six species of Sida L. viz., S. alnifolia L., S. beddomei Jacob., S. fryxelli Sivar. & Pradeep., S. rhomboidea Roxb. ex. Flemming., and S. keralensis E. S. S. Kumar, Shailaja, Sreekala, Parthipan & R. Prakashkumar sp. nov. Materials and methods: Field explorations were carried out in Kerala, India, and root samples of different species were collected, shade-dried, and powdered. The powdered root samples of each species were analyzed using Atomic Absorption Spectrophotometer (AAS), and Flame Photometer. Results: The presence of Sodium (Na), Potassium (K), Calcium (Ca), Magnesium (Mg), Iron (Fe), Zinc (Zn), Manganese (Mn), Copper (Cu), Cadmium (Cd), Chromium (Cr), Nickel (Ni), and Lead (Pb) were detected in the species of Sida L. under study. The most abundant macro-element was detected as K, ranging from 15,630±0.21 mg kg−1 in S. rhomboidea to 24,910±0.14 mg kg−1 in S. beddomei. Among the micro-elements, Fe was present in higher concentrations ranging from 461.7 ± 193.96 mg kg−1 in S. cordata to 1363.93±192.90 mg kg−1 in S. beddomei. Toxic metals like Cr, Cd, Ni, and Pb were below detectable levels. Conclusion: The elemental composition of the species under study was quite different but within the permissible limits recommended by WHO. The current study revealed that the species of Sida L. under study could be valuable for Ayurvedic practitioners and traditional healers in developing herbal formulations.